2014
DOI: 10.2514/1.c032154
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Route Optimization for Formation Flight

Abstract: We quantify the fuel and cost benefits of applying extended formation flight to commercial airline operations. Central to this study is the development of a bi-level, mixed integer-real formation flight optimization framework. The framework has two main components: 1) a continuous domain aircraft mission performance optimization and 2) an integer optimization component that selects the best combination of optimized missions to form a formation flight schedule. The mission performance reflects the effects of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…For a constant lift coefficient this results in a reduction in induced drag [1]. Numerous research studies, ranging from numerical simulation studies to wind tunnel testing and in-flight demonstrations, have highlighted the potential fuel saving benefits of formation flight for commercial aircraft.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a constant lift coefficient this results in a reduction in induced drag [1]. Numerous research studies, ranging from numerical simulation studies to wind tunnel testing and in-flight demonstrations, have highlighted the potential fuel saving benefits of formation flight for commercial aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their approach assumes that formation flight also affects the zero lift drag coefficient which is not the case in reality. Xu et al [1] also investigate aircraft route optimization for formation flight. In their study, the induced drag coefficient of an aircraft in formation flight is calculated beforehand based on an aerodynamic model as a function of various parameters (lift coefficient, position in the formation, formation type).…”
Section: Introductionmentioning
confidence: 99%
“…Section VI considers the impact on timing and introduces scheduling constraints. Studies based on individual pairings, looking only at the routing problem, have shown potential positive tradeoffs between the diversion to join formation and the reduction in drag formation flight produces [19][20][21][22][23][24]. Formation routes for five aircraft studied by Bower et al [4] focus on aerodynamic aspects such as wing tip separation.…”
Section: Introductionmentioning
confidence: 98%
“…These prior works adopt numerical trajectory optimization techniques [25][26][27] to calculate high-fidelity solutions to the routing problem. Once the routing problem is solved, evaluating the cost for each potential formation, the subsequent assignment problem is readily solved by a discrete optimization [20].…”
Section: Introductionmentioning
confidence: 99%
“…7 In either case, advanced flight control techniques are required to ensure optimal trajectories of the vortex-generating and the follower aircraft, 8 particularly with adverse atmospheric conditions. From the point of view of airframe design, unexpected WVE can lead to large dynamic loads that create structural integrity risks.…”
Section: Introductionmentioning
confidence: 99%